Strategi Komunikasi Pemasaran Bubur Mang Oyo melalui Penerapan Elemen Pemasaran Viral dalam Menarik Konsumen - Muhammad Dinnar Abdul Malik -; Ulfa Yuniati - (JEBIM Prima, 2020)
The era of information communication technology development or the era of disruption 4.0 has an impact on marketing strategies. Currently, the marketing strategy carried out by entrepreneurs is no longer conventional but uses modern communication strategies which use the internet as a tool to market products or services to consumers. This is what the owner of Bubur Mang Oyo does in promoting his products with the image of Porridge Behind Does not Spill. The purpose of this study was to determine the marketing communication strategy of Mang Oyo Porridge through the application of viral marketing elements with the image of the porridge behind it not spilling. The type of research used is qualitative with a case study approach using a single case. Data collection techniques using interviews and observations. The results of this study indicate that the marketing communication strategy through the application of viral marketing elements by Bubur Mang Oyo includes (1) mango porridge has given its products free of charge to consumers, (2) it is easy to share due to its marketing through Instagram social media, (3) ) use the image behind not spilling, service, design, to attract consumers, (4) and take advantage of existing networks, namely consumers who have come and eat to market through mouth to mouth or their networks on social media.